Mutation and methylation status of KIT and TP53 in canine cutaneous and subcutaneous mast cell tumours - Vozdova, Miluse; Kubickova, Svatava; Fictum, Petr; Cernohorska, Halina; Fröhlich, Jan; Rubes, Jiri (Veterinary and comparative oncology, 2020)
Cutaneous and subcutaneous mast cell tumours (MCTs) are counted among the most frequent cancers in dogs. However, the genetic aetiology of their development is still mostly unknown, with the exception of KIT and tumor protein p53 (TP53 ) mutations reported in less than a half of cutaneous MCTs. In subcutaneous MCTs, no gene alterations were previously detected. We analysed KIT and TP53 mutations in cutaneous and subcutaneous MCTs, and identified methylated CpG sites in KIT and TP53 promoters and adjacent exon 1 regions. The mutation analysis focused on KIT exons 8, 9 and 11, and TP53 exons 5-8, and revealed mutations in 26% and 7% cutaneous MCT cases, respectively. Moreover, we report a first case of KIT mutation ever detected in subcutaneous MCTs. KIT exon 11 mutations and high Kiupel and Patnaik grades were associated with reduced survival in this study. Both KIT and TP53 gene were generally unmethylated in canine cutaneous MCTs. A sporadic methylation of the CpG positions in KIT promoter and adjacent exon 1 was detected in 70.4% of cutaneous and 82% of subcutaneous MCTs. A sporadic methylation of the CpG positions in the TP53 promoter and exon 1 was observed in 36.8% of the analysed cutaneous MCT samples. Only in two subcutaneous MCTs, we observed more than 30% of clones showing KIT methylation at the CpG positions 13 or 14. The CpG position 14 is involved in a predicted binding site for Sp1 transcription factor. However, the significance of KIT promoter methylation at this specific position needs further evaluation.
Keywords: nádorový supresorový protein p53; TP53; Survival; psi; Skin Neoplasms; přežití; protoonkogenní proteiny c-kit; Dogs; subkutánní tkáň; mutace; Tumor Suppressor Protein p53; mast cell tumour; Dog Diseases; Proto-Oncogene Proteins c-kit; dog; nemoci psů; Subcutaneous Tissue; Mastocytosis, Cutaneous; zvířata; Mutation; promoter; nádory kůže; pilotní projekty; methylation; kožní mastocytóza; Pilot Projects; mutation; KIT; Animals